John Ruskin and Climate - Orestano, Francesca (English Literature)
The essay offers an analysis of John Ruskin’s 1884 lectures on The Storm-Cloud of the Nineteenth Century, focusing on his notions about the phenomenon of the storm-cloud, his careful recording of its occurrence in various parts of England since the 1870s, and his search for its causes and meaning. Even though in the eyes of his contemporaries the arguments expounded by Ruskin might have sounded confused, and devoid of scientific logic, his concern was genuine, and his climate observations and notions, albeit lacking the scientific explanation of the phenomenon, were correct insofar as they attributed the presence of the black malignant cloud to man’s perverse management of nature and its resources. Such condition, mainly dating from the rise of Industrial revolution, has earned the name of Anthropocene, thus defining the era in which the human impact on Earth has reached critical levels. Ruskin’s lectures can be read as an early foray in cultural climatology, he being a fellow in ecocriticism, a proto-environmentalist, very much alert to men’s moral responsibility towards nature. In addition, the essay focuses on Ruskin’s critique of scientific language, and on the apparent contradictions marking his discourse, as the most remarkable aspect of his analytical procedure. Such aporias led to a significant widening of the epistemic horizon, where nothing, including science and chemistry, prophecy and passion, religion and myth, would be lost or undervalued.